2017
DOI: 10.1111/1365-2435.12941
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation by leguminous shrubs increases along a precipitation gradient

Abstract: Abstract1. Combining nutrient dynamics (plant nutrient uptake and soil fertility) can help uncover mechanisms of shrub-grass interactions and assess the validity of the stressgradient hypothesis, which predicts that facilitation between plants increases in stressful environments. However, how facilitation via shrub-mediated nutrient increases varies with precipitation is poorly resolved.2. We first synthesized a global dataset from 66 studies and evaluated how shrubs affected soil organic carbon (C) and nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…These factors were notably and positively related to T. chinensis coverage based on the Pearson correlation test (r = 0.4-0.7, see Appendix 1), indicating soil fertility increased with T. chinensis coverage, and confirming the existence of the facilitation effect. Previous studies also demonstrated that net facilitation effect was more likely to occur in stressful environments 39 . Specifically, the formation of fertile islands is an important process driving the positive interactions between shrubs and grass 39 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These factors were notably and positively related to T. chinensis coverage based on the Pearson correlation test (r = 0.4-0.7, see Appendix 1), indicating soil fertility increased with T. chinensis coverage, and confirming the existence of the facilitation effect. Previous studies also demonstrated that net facilitation effect was more likely to occur in stressful environments 39 . Specifically, the formation of fertile islands is an important process driving the positive interactions between shrubs and grass 39 .…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies also demonstrated that net facilitation effect was more likely to occur in stressful environments 39 . Specifically, the formation of fertile islands is an important process driving the positive interactions between shrubs and grass 39 .…”
Section: Discussionmentioning
confidence: 88%
“…In this context, the preserved forest can provide protection from solar radiation and frost, as well as increased water content and litter accumulation, with the consequent increase in nutrients (Abiyu et al 2017). In particular, leguminous plants often provide litter with a high content of nutrients, mainly nitrogen, and facilitate the establishment and growth of other species (Avendaño‐Yáñez et al 2018; Zhang et al 2018 b ). Our results partially support these findings, because the preserved forest had higher nitrate and organic matter values than the degraded forest, whereas in the latter, nitrate and organic matter slightly increased from plots with herbaceous vegetation to microsites under shrubs, with the highest values being recorded under the leguminous spiny shrub.…”
Section: Discussionmentioning
confidence: 99%
“…It can be expected, however, that the differential use of different essential resources by neighbor plants influences the outcome of their interaction (Tilman, 1982). Surprisingly, the experimental assessment of both the independent and joint effects of the availability of several essential soil resources on grass–shrub interactions, and on plant interactions in general, is scarce, yet findings so far suggest that the response of the plant interactions may not be consistent for the various resources considered (e.g., le Bagousse‐Pinguet et al, 2013; Wilberts et al, 2014; Zhang, Lü, et al, 2018), even for different sources of nitrogen (Trinder et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relative importance of the mechanisms involved in herbaceous–woody plant interactions often changes as plants age, resulting in ontogeny‐mediated shifts in the outcome of the interactions, which in turn may vary in response to variations in abiotic conditions (le Roux et al, 2013; Soliveres et al, 2010). Overall, a growing body of literature points to the interplay between multiple factors regulating grass–shrub coexistence and interactions, yet there are still very few insights about the relative role and combined effects of the factors involved (Cipriotti et al, 2014; le Roux et al, 2013; Soliveres et al, 2015; Zhang, Lü, et al, 2018). The understanding of such interplay remains very limited, hampering our ability to predict the response of herbaceous–woody assemblages to changing climatic and disturbance regimes, and incorporate this knowledge into land management and restoration actions.…”
Section: Introductionmentioning
confidence: 99%